Prediction of Escapism Based on Interpersonal Sensitivity, Self-Criticism, and the Need for Social Approval - Athari, Nasibeh; Abazari, Arezo; Rashki, Masoumeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to examine the predictive roles of interpersonal sensitivity, self-criticism, and the need for social acceptance in escapism among individuals in Tehran.Methods and Materials: A cross-sectional design was employed with a sample of 250 participants, selected based on the Morgan and Krejcie table. Data were collected using standard scales: the Escapism Scale, Interpersonal Sensitivity Measure (IPSM), Self-Criticism Scale (SCS), and the Need for Social Approval Scale. Pearson correlation analysis was conducted to assess the relationships between escapism and the predictor variables, and a multiple regression analysis was used to examine the combined predictive power of interpersonal sensitivity, self-criticism, and the need for social acceptance on escapism. Analyses were performed using SPSS version 27.Findings: The results revealed significant positive correlations between escapism and interpersonal sensitivity (r = 0.41, p < 0.001), self-criticism (r = 0.52, p < 0.001), and the need for social acceptance (r = 0.35, p = 0.002). Multiple regression analysis showed that all three predictors significantly contributed to the model (F = 74.54, p < 0.001, R² = 0.46, adjusted R² = 0.45). Self-criticism was the strongest predictor (β = 0.37, p < 0.001), followed by interpersonal sensitivity (β = 0.23, p < 0.001) and the need for social acceptance (β = 0.16, p < 0.001).Conclusion: This study highlights the significant roles of self-criticism, interpersonal sensitivity, and the need for social acceptance in predicting escapism. These findings suggest the importance of addressing these psychological factors in therapeutic and educational interventions to promote healthier coping mechanisms.